New hedging mechanism - Capacity Transfer Rights in MISO's capacity market - Xianjun Zhang; Mili, Joseph; Karki, Mahesh; Chatterjee, Dhiman; Zhongyu Wu; Cheng Luo (IEEE Power & Energy Society General Meeting, 2016)
The locational mechanisms in MISO's capacity market may result in price separation between different capacity zones due to constraints in limiting capacity transfers between capacity zones. Managing this price separation risk is identified as one of the issues in MISO's resource adequacy construct. A new financial property right, Capacity Transfer Right (CTR), is proposed to hedge against this price separation and reduce the exposure when congestion occurs in the locational capacity market. CTRs allocate the excess revenue collected from the settlement process of annual capacity resource auction primarily to the CTR holders with long-term supply arrangements. In an attempt to fund the hedges in a just and reasonable manner a priority based methodology was proposed for the allocation of the excess revenue to fund granted CTRs. This will increase the likelihood that CTRs from historical long-term supply arrangements and more recent long-term supply arrangements will be fully funded.